2022
DOI: 10.1063/5.0083743
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of bluff body flow structures in variable velocity flows

Abstract: The present study explores three-dimensional vortex-dynamics past a wall-attached bluff body kept in a variable velocity field with numerical simulations. A trapezoidal pulse of mean velocity, consisting of acceleration phase from rest followed by constant velocity phase and deceleration phase to rest, is imposed at the inlet of the computational domain similar to the experimental study of Das et al. [“Unsteady separation and vortex shedding from a laminar separation bubble over a bluff body,” J. Fluids Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Since the inlet velocity profiles are built upon the assumption of a two-dimensional channel, using a subdomain guarantees the application of a slip boundary on the sidewalls. The work of Sarath & Manu (2022) provides additional information about the procedure to obtain the inflow velocity profile.…”
Section: Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the inlet velocity profiles are built upon the assumption of a two-dimensional channel, using a subdomain guarantees the application of a slip boundary on the sidewalls. The work of Sarath & Manu (2022) provides additional information about the procedure to obtain the inflow velocity profile.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…In contrast, the other instability develops in the braid region with a higher spanwise wavenumber. Recently, by analysing the three-dimensional coherent structures arising in the wake of a wall-attached body, Sarath & Manu (2022) showed that the vortices shed from boundary layers displayed simultaneously both elliptical and hyperbolic instability.…”
Section: Introductionmentioning
confidence: 99%